ROBOTIC COMPARED WITH LAPAROSCOPIC CHOLECYSTECTOMY: A PROPENSITY MATCHED ANALYSIS - Kane, William J. (Surgery, 2019)
BACKGROUND: As robotic surgery becomes more ubiquitous, determining clinical benefit is necessary in order to justify the cost and time investment required to become proficient. We hypothesized that robotic cholecystectomy would be associated with improved clinical outcomes but also increased cost as compared with standard laparoscopic cholecystectomy. MATERIALS AND METHODS: All patients undergoing robotic or laparoscopic cholecystectomy at a single academic hospital between 2007-2017 were identified using an institutional clinical data repository. Patients were stratified by operative approach (robotic vs. laparoscopic) for comparison and propensity score-matched 1:10 based on relevant comorbidities and demographics. Categorical variables were analyzed by Chi-square test and continuous variables using Mann-Whitney U test. RESULTS: 3,255 patients underwent cholecystectomy during the study period. There were no differences in demographics or BMI, but greater rates of diabetes mellitus, hypertension, and gastroesophageal reflux disease were present in the laparoscopic group. After matching (n=106 robotic, n=1060 laparoscopic), there were no differences in preoperative comorbidities. Patients who underwent robotic cholecystectomy had lesser durations of stay (Robot: 0.1±0.7 vs. Lap: 0.8±1.9, p < 0.0001) and lesser 90-day readmission rates (Robot: 0% [0], Lap: 4.1% [43], p = 0.035); however, both operative and hospital costs were greater compared with laparoscopic cholecystectomy. CONCLUSIONS: Robotic cholecystectomy is associated with lesser duration of stay and lesser readmission rate within 90-days of the index operation, but also greater operative duration and hospital cost compared with laparoscopic cholecystectomy. Hospitals and surgeons need to consider the improved clinical outcomes but also the monetary and time investment required prior to pursuing robotic cholecystectomy.